2020
DOI: 10.1038/s41598-020-63469-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of nucleotide binding domain-like receptor protein 3 (NLRP3) increases susceptibility of total urinary arsenic to renal cell carcinoma

Abstract: our study showed that total urinary arsenic concentrations were positively correlated with renal cell carcinoma (RCC). Chronic inflammation is a key player in the development of RCC. This study explored the association between nucleotide-binding domain-like receptor protein 3 (NLRP3) genotypes and the development of RCC. We also investigated whether any of the NLRP3 genotypes modified the risk between arsenic and RCC. We recruited 350 RCC patients and 700 age-sex matched controls. RCC was confirmed by patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Hence, the effect of NLRP3 rs4925650 GA/AA genotypes and NLRP3 rs10157379 CT/TT genotypes on susceptibility to CKD appears to be independent of age, sex, educational level, consumption of tea, alcohol, and coffee, analgesic usage, and disease histories of diabetes and hypertension. The present study found an association between the NLRP3 rs10157379 CT/TT genotypes and CKD in the Taiwanese population, which is in accordance with our previous research showed that the NLRP3 rs10157379 T allele has a borderline association with renal cell carcinoma 43 . These results imply that subjects with NLRP3 rs10157379 T allele may be associated with renal damage than those with C allele.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the effect of NLRP3 rs4925650 GA/AA genotypes and NLRP3 rs10157379 CT/TT genotypes on susceptibility to CKD appears to be independent of age, sex, educational level, consumption of tea, alcohol, and coffee, analgesic usage, and disease histories of diabetes and hypertension. The present study found an association between the NLRP3 rs10157379 CT/TT genotypes and CKD in the Taiwanese population, which is in accordance with our previous research showed that the NLRP3 rs10157379 T allele has a borderline association with renal cell carcinoma 43 . These results imply that subjects with NLRP3 rs10157379 T allele may be associated with renal damage than those with C allele.…”
Section: Discussionsupporting
confidence: 93%
“… 31 It has been shown that the C allele of NLRP3 rs1539019 significantly increased the risk of renal cell carcinoma, and the genotype of CC was associated with increased renal cell carcinoma risk compared with AA genotype. 32 Previous studies suggested that the CC genotype of NLRP3 rs1539019 was not associated with altered major blunt trauma risk 33 and coronary heart disease risk. 34 In our study, we demonstrated that the CC genotypes at NLRP3 rs1539019 were not associated with CWP risk in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 97%
“…Some NLRP3 gene variants (e.g. rs7512998 ) are significantly associated with hypertension [ 39 ]. Consequently, we may hypothesize that the outcome of COVID-19 is aggravated by the presence of T2DM, obesity and hypertension because patients with those conditions show an activated NLRP3 inflammasome which is probably further activated by the infection.…”
Section: Discussionmentioning
confidence: 99%